Employability Skills for Entry Level Workers: A Content Analysis of Job Advertisements in Indonesia - Suarta, I Made; Suwintana, I Ketut; Sudhana, I G P Fajar Pranadi; Hariyanti, & Ni Kadek Dessy (Journal of Technical Education and Training, 2018)
The changing world of work is creating new challenges for employers and employees. Employers expect new workers to have a broader range of competencies and ability, strong job specific skills and employability skills. Workers entry skills that are demanded by employers may be influenced by many factors including nature of work and culture of society. The objectives of this study were to examine the labour market demand on skills as typically highlighted in job advertisements in Indonesia, and to develop a conceptual framework for employability skills. The research was conducted using content analysis method, a commonly used method in studies of job advertisements. The content analysis of job advertisements is used to identify a wide range of employability skills needed by todayâ€™s labour market. The job advertisements were collected from major newspapers (published daily) that are circulated nation-wide, during February to July 2017. There are 57 job advertisements analysed. In this research, employability skills framework refer to a set of generic skills and personal attributes. The research identified 272 key terms for employability skills requirements, consisting of 191 key terms for generic skill and 81 key terms for personal attributes.  In most job advertisements, employers place highest value on employability skills and lowest value on academic qualifications. Communication skills, self management skills, teamwork skills, creativity and innovation skills, and problem-solving skills are the top five of the generic skills most frequently requested in the job advertisements. Personal attributes are personal characteristics based on behaviors and attitudes that can not be separated with generic skills, including: honesty, independence, accuracy, appearance, ethics and behaviors, openness, and other characters.